«Մանկութեան աւետարան»-ի և Հակոբոսի նախաավետարանի հայերեն թարգմանությունները - Մամյան, Մարի («Նաիրի» հրատ.)
―Протоевангелие Иакова‖, также как созданное на основе этого апокрифа армянское ―Евангелие Детства‖, представляют в основном рождение и детство Марии и Иисуса. Однако, армянское ―Евангелие Детства‖ отличается от ―Протоевангелия‖ несколькими существенными особенностями. Эти особенности проявляются в сценах Благовещения (необычный диалог с ангелом), Рождения Христа (появление праматери Евы) и Поклонения волхвов (имена магов). Этим армянское ―Евангелия Детства‖ отличается не только от ―Протоевангелия‖, но и от других аналогичных апокрифов. Благодаря им не только решаются вопросы, связанные с происхождением армянского ―Евангелия Детства‖, но и выявляются отраженные в нем догматические идеи, относящиеся к наиболее важным аспектам христианского вероучения (идея о вечном девстве Марии, идея спасения, идея воплощения Христа). The Protoevangelium of James, as well as the Armenian Gospel of the Infancy created on the basis of this apocryphon, present the birth and childhood of Jesus and Mary. Yet, the Armenian Gospel of the Infancy contains a number of essential differences from the Protoevangelium. The differences between these two apocryphal writings, which are of ideological nature, appear in the episodes of the Annunciation (unordinary dialogue with the angel), the Nativity of Christ (the appearance of the foremother Eve), and the Adoration of the Magi (the names of the Magi). The aforementioned differences emphasize the uniqueness of the Armenian Gospel of the Infancy in comparison not only to the Protoevangelium, but also to other analogous gospels. Thanks to them, we can not only clarify the essential questions related to the origins of the Armenian Gospel of the Infancy, but also reveal the dogmatic ideas reflected in this apocryphon, which mainly belong to the more important aspects (the idea of the Perpetual Virginity of Mary, the idea of Salvation, the idea of the Incarnation of Christ) of the Christian doctrine.
Keywords: Բանասիրություն